Scope of sedition under Provision124A of the Indian penal code in Modern India: Comparative Analysis and Future Prospects for Legal Reform (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper explores the scope and application of Section 124A of the Indian Penal Code, which defines and penalizes sedition, analyzing its relevance in the context of modern democratic principles and its implications on free speech and dissent. Originally introduced during the colonial era, Section 124A has continued to play a significant role in managing internal security but has increasingly sparked debates concerning its alignment with democratic ideals and freedom of expression. This study examines how Indian courts have interpreted sedition laws, often oscillating between national security and the protection of civil liberties. A comparative analysis with sedition laws in other democracies, including the United States and the United Kingdom, reveals varying approaches to balancing state security and individual freedoms. Through these comparisons, the study highlights potential pathways for legal reform in India, advocating for a narrowed definition of sedition that aligns with international standards on free speech while addressing genuine threats to national security. This paper ultimately proposes specific policy recommendations aimed at reforming Section 124A to foster a legal framework that safeguards democratic discourse, upholds the right to dissent, and preserves public order in a manner consistent with India’s constitutional principles.